The transcription factor BATF modulates cytokine-mediated responses in T cells. (August 2016) - Sopel, Nina; Graser, Anna; Mousset, Stephanie; Finotto, Susetta
Highlights: In this review we integrate the recent findings on the transcription factor BATF, which plays a crucial role in Th17 and Tfh differentiation and influences Th2 and Th9 responses. Moreover, BATF is essential for immunoglobulin class-switch recombination, as well as for CD8 + T cell mediated anti-viral effector function. Furthermore, mice with Batf-deficiency have been shown to be protected from experimental models of allergic asthma, thus identifying BATF as an interesting target for novel therapeutic strategies against this allergic disease. Abstract: The transcription factor BATF ( basic leucine zipper transcription factor, ATF-like ), belongs to the AP-1 family of transcription factors and has been shown to be predominantly expressed in cells of haematopoietic origin, especially in B and T cells. In studies using Batf-deficient mice, a profound defect in the differentiation of T helper cells type 17 (Th17) and follicular T helper cells (Tfh) was described, as well as an impairment of antibody production with switched isotypes. More recently BATF has been described to influence also Th2 and Th9 responses in models of murine experimental asthma. In CD8 + T cells BATF has been found associated with anti-viral responses. This review summarizes the role of BATF in CD4 + T cell subsets and in CD8 + T cells, with particular focus on this transcription factor in the setting of allergic asthma.